Tropospheric Ozone A Hazard for Vegetation and Human Health - Agrawal, Shashi Bhushan; Agrawal, Madhoolika; Singh, Anita (Cambridge Scholars Publishing, 2021)
This book presents updated and relevant information on the tropospheric ozone problem and its effects on the plants and human health. The contributions here present in-depth knowledge about history, pattern, sources, environmental factors and other necessary aspects of the tropospheric ozone problem. The book provides a balanced view of current developments on the effects of the tropospheric ozone on plant and human health, crop production and ecosystem services. In addition to the effects of the tropospheric ozone on growth and physiological and biochemical traits, it also considers the molec.